Water reuse for aquaculture: Comparative removal efficacy and aquatic hazard reduction of pharmaceuticals by a pond treatment system during a one year study - Fedorova, Ganna; Grabic, Roman; Grabicová, Kateřina; Turek, Jan; Van Nguyen, Tuyen; Randak, Tomas; Brooks, Bryan W; Zlabek, Vladimir (Journal of hazardous materials, 2022)
Aquaculture is increasing at the global scale, and beneficial reuse of wastewater is becoming crucial in some regions. Here we selected a unique tertiary treatment system for study over a one-year period. This experimental ecosystem-based approach to effluent management included a treated wastewater pond (TWP), which receives 100% effluent from a wastewater treatment plant, and an aquaculture pond (AP) that receives treated water from the TWP for fish production. We examined the fate of a wide range of pharmaceutically active compounds (PhACs) in this TWP-AP system and a control pond fed by river water using traditional grab sampling and passive samplers. We then employed probabilistic approaches to examine exposure hazards. Telmisartan, carbamazepine, diclofenac and venlafaxine, exceeded ecotoxicological predicted no effect concentrations in influent wastewater to the TWP, but these water quality hazards were consistently reduced following treatment in the TWP-AP system. In addition, both grab and passive sampling approaches resulted in similar occurrence patterns of studied compounds, which highlights the potential of POCIS use for water monitoring. Based on the approach taken here, the TWP-AP system appears useful as a tertiary treatment step to reduce PhACs and decrease ecotoxicological and antibiotic resistance water quality hazards prior to beneficial reuse in aquaculture.
Keywords: rybníky; léčivé přípravky; Aquaculture; Pharmaceutical Preparations; Ecosystem; Environmental Monitoring; Probabilistic hazard assessment; Biological pond; zvířata; Pharmaceutical fate; Wastewater; POCIS; monitorování životního prostředí; Waste Water; Ponds; voda; Water Pollutants, Chemical; Tertiary treatment; Water; odpadní voda; vodní hospodářství; Animals; chemické látky znečišťující vodu; ekosystém